DEVELOPING AN INTEGRATED EDUCATIONAL MANAGEMENT MODEL FOR BULLYING PREVENTION IN PESANTREN: A GROUNDED THEORY APPROACH TO COMMUNITY RESILIENCE AND COLLECTIVE HEALING - Mujiburrohman Mujiburrohman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study develops an Integrated Educational Management Model for Bullying Prevention (IEMMBP) in Indonesian pesantren through a grounded theory approach, with a focus on community resilience and collective healing as culturally embedded mechanisms of protection and recovery. Data were collected through in-depth interviews, participant observation, focus group discussions, and document analysis across four pesantren representing diverse governance structures in Java and Madura. The analysis followed Strauss and Corbin’s coding procedures—open, axial, and selective—supported by constant comparative analysis until theoretical saturation was achieved. The findings reveal that bullying prevention in pesantren is most effective when institutional management, spiritual authority, and communal practices are integrated into a single governance ecosystem. Three core theoretical categories emerged: (1) institutional integration as the structural foundation of prevention, (2) community resilience as a protective social mechanism, and (3) collective healing as a transformational process of recovery and reintegration. The resulting model reframes bullying not merely as individual misconduct, but as a disruption of moral order and collective dignity that requires restorative, not solely punitive, solutions. The study contributes to educational management, resilience theory, and Islamic education studies by offering a non-Western, community-based alternative to conventional anti-bullying frameworks. It also provides practical implications for pesantren policymakers, the Ministry of Religious Affairs, and Southeast Asian boarding school systems seeking culturally grounded, trauma-informed strategies for student wellbeing and institutional safety.